Novel anion-bound borates as lubricant additives - Shaw, Katherine (2016)
Effective anti-wear lubricant additives are highly desirable in order to improve the performance and lifetime of automotive engines and transmission systems, whilst keeping in line with environmental standards. Although there has been recent research interest into the use of additives containing both boron and phosphorus, the field is rather underdeveloped and there is much scope for further exploration of this area. To this end, this thesis describes the synthesis and anti-wear testing of a series of novel phosphate-bound borate potential lubricant additives.